2000
DOI: 10.3923/pjbs.2000.1177.1179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sowing Methods and Seed Rates on Grain Yield and Yield Components of Wheat Variety Pak-81

Abstract: The results revealed that sowing method greatly affected the number of fertile tillers, biological yield, grain yield and harvest index value whereas grain spikeG 1 and 1000-grain weight were non significant. Among the method pore method supersede broadcast method. Similarly seed rates also highly significantly affected the grain yield and yield components except 1000-grain weight. Seed rate of 175 kg haG 1 produced grain yield of 5325. 13 kg haG 1 and proved to be the most economical seed rate. Though the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 1 publication
5
15
0
Order By: Relevance
“…Tiller number were the highest with 300 kg seeds ha −1 at the maturity stage, and when levels exceeded 300 kg seeds ha −1 the tiller number decreased. The seeding rate is a key management factor that influences the production and survival of tillers (Tilley et al, 2019) and tiller number per unit area is known to increase with increasing seeding rate up to a certain limit (Dai et al, 2013;Iqbal et al, 2012;Khan et al, 2000;Otteson et al, 2008), which was in accordance with our results. In the present study, the combination of the wide-space sowing method and a seeding rate of 300 kg seeds ha −1 improved tiller formation and grain yield.…”
Section: Discussionsupporting
confidence: 92%
“…Tiller number were the highest with 300 kg seeds ha −1 at the maturity stage, and when levels exceeded 300 kg seeds ha −1 the tiller number decreased. The seeding rate is a key management factor that influences the production and survival of tillers (Tilley et al, 2019) and tiller number per unit area is known to increase with increasing seeding rate up to a certain limit (Dai et al, 2013;Iqbal et al, 2012;Khan et al, 2000;Otteson et al, 2008), which was in accordance with our results. In the present study, the combination of the wide-space sowing method and a seeding rate of 300 kg seeds ha −1 improved tiller formation and grain yield.…”
Section: Discussionsupporting
confidence: 92%
“…-1 revealed remarkably least number kernels spike -1 . It was noticed that increasing seeding rate, the number of kernels spike -1 decreased Khan et al (2002). These results are in agreement with those obtained by (Iqbal et al, 2012;Said et al, 2012;Abd El-Lattief, 2014;Nizamani et al, 2014;El-Hag, 2016;Shah et al, 2016;Mekomen, 2017;Mohiy and Salous, 2018) whom reported that grain yield and its components significantly differed according to different seeding rate.…”
Section: Effect Of Seeding Ratesupporting
confidence: 88%
“…This outcome also in line with [18] who explained that lower plant population levels significantly increased the number of grains per spike. Khan et al,, [45,46] concluded that by increasing seed rate the 1000-grains weight is reduced. These results are in analogy with the findings of earlier works of Arif et al, [11] who reported higher yield with seed rate of 150 kg ha -1 .…”
Section: The Effect Of Plant Populations On Yield Components Of Bread...mentioning
confidence: 99%